KRAS突变的非小细胞肺癌的研究进展 (Zhongguo Fei Ai Za Zhi, 2018)
Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) accounts for 80%-85% of all patients with lung cancer, the majority of patients with lung cancer at the time of diagnosis is in the advanced stage. The development of target therapy based on has changed the mode of treatment in patients with advanced NSCLC. In NSCLC, epidermal growth factor receptor mutation (EGFR) fusion with echinoderm microtubule-associated protein-like4-anaplastic lymphoma kinase (EML4-ALK) has been shown to be a powerful biomarker. It is well known that KRAS is also NSCLC one of the most common mutations in oncogenes, although more than 20 years ago KRAS mutation was found in NSCLC. At present, although there are many drugs used to treat NSCLC patients with KRAS mutation, there is no selective or specific inhibitor for the direct elimination of KRAS activity. NSCLC patients with KRAS mutation have poor responsiveness to most systemic therapy. However, individualized therapy for activated signaling pathways with targeted drugs has a good effect on the prognosis of NSCLC patients with KRAS mutation. In addition, the prognostic and predictive role of KRAS mutation in NSCLC remains unclear. In this review, we focus on the research progress of NSCLC with KRAS mutation, including molecular biology, clinicopathological features, prognosis and prediction of KRAS mutation, which will help to improve the understanding of NSCLC in KRAS mutation.